Risk Assessment of Public Electric Vehicle Battery Swapping Station (SPBKLU) - Fata Herzasha, Azkal (Journal of Economics and Business UBS, 2023)
The use of Electric Vehicles (EVs) in recent years has become an alternative for people to switch to environmentally friendly technology. Exhaust emissions from Internal Combustion Engines (ICE) vehicle which play a big role in air pollution are one of the strong reasons for people to switch. However, one of the main challenges faced when using EVs widely is the limited range and long battery charging times. The existence of limited electric vehicle infrastructure is also an obstacle to the sustainability of the use of EVs for daily activities. Public Electric Vehicle Battery Swapping Station/Stasiun Penukaran Baterai Kendaraan Listrik Umum (SPBKLU) are one of the potential solutions to this problem that allow EV owners to quickly swap out their depleted batteries for fully charged ones. This research study aims to determine the potential risks that can arise in the development process of the Public Electric Vehicle Battery Swapping Station (SPBKLU) as a solution to the limited range and charging time of battery – based electric motor vehicles. The data collection method was carried out through interviews and surveys to 3 respondents from divisions/units who are owners of business processes related to the SPBKLU project. A comprehensive risk assessment through risk management assessment is carried out on the strategic, financial, operational, project and compliance aspects of this technology. The risks that have been identified are then evaluated and prioritized to then be able to make a mitigation plan in reducing the level of risk to reach the level of corporate risk appetite. The results of the risk assessment identified 16 (sixteen) risks with different levels of risk as follows, there is 2 (two) risks at the Extreme level, 3 (three) risks at the Very High level, 9 (nine) risks at the High level, and 2 (two) risks at the Moderate level. Based on the Risk Appetite level of PT PLN (Persero), only 2 (two) risks that are at the Moderate level will be accepted. Meanwhile, for the other 14 (fourteen) risks, a mitigation plan will be carried out to lower the risk level to a Moderate/ Low level. The mitigation plan that will be carried out is prepared in the form of an action plan that the implementation process will be monitored according to the scheduled timeline.